BaDuShengJi hydrogel accelerates diabetic wounds healing and regeneration of deep burn injury by anti-bacteria, anti-inflammation and promoting epithelialization - Zhang, Yuxiang; Yu, Yuanyuan; Yu, Lien; Wang, Fang; Yang, Fuwei; Liang, Shiyu; Xu, Wen; Ji, Mengying; Geng, Yinuo; Xue, Jingwei; Han, Chunmao; Zhang, Zhongtao; et al. (Frontiers in Pharmacology, 2025)
Bacterial infection, excessive inflammation, and delayed re-epithelialization are the biggest obstacles to diabetic wound healing and burn injuries. As a classic prescription, BaDuShengJi San (BDS) has been proven to accelerate chronic wound healing through anti-bacterial and anti-inflammatory mechanisms. However, there are few reports on its role in preventing the malignant progression of deep burns or accelerating deep burn wound healing. Furthermore, the powder formulation of BDS has limited application scenarios, difficult dosage control, potential environmental pollution, and contradiction with the theory of moist wound healing, which has constrained its scope of application and efficacy to some extent. To address these issues, this study developed a novel hydrogel formulation incorporating BDS using carbomer 940 as the gel matrix, glycerol as a humectant, and triethanolamine as a pH adjuster, through orthogonal design. The results demonstrated that the prepared BDS-loaded gel (BDN) exhibited excellent stability and good biocompatibility, preserving the antibacterial and angiogenesis-promoting properties of BDS while enhancing its anti-inflammatory capabilities. Additionally, BDN significantly accelerated re-epithelialization in diabetic chronic wounds and burn wounds compared to BDS, achieving superior healing quality and mitigating renal damage associated with long-term BDS application. This study provides a comprehensive strategy for accelerating wound healing in diabetic chronic wounds and deep burn injuries and offers insights into expanding the clinical application of BDS and enhancing its therapeutic effects.